Piezo2 expressed in proprioceptive neurons is essential for skeletal integrity - Eran Assaraf (Nature Portfolio, 2020)
Mutations in human PIEZO2, encoding for a mechanosensitive ion channel, lead to skeletal abnormalities including scoliosis and hip dysplasia. Here, the authors show that deletion of Piezo2 in proprioceptive neurons, but not in skeletal lineages, recapitulated the human phenotype in mice.